Interactions of Disulfide-deficient Selenocysteine Analogs of μ-Conotoxin BuIIIB with the Voltage-Gated Sodium Channel Na(V)1.3 - Green, Brad R. (2014)
Inhibitors of the neuronal voltage-gated sodium channel subtype Na(V)1.3 are of interest as pharmacological tools for the study of neuropathic pain associated with spinal cord injury and have potential therapeutic applications. The recently described μ-conotoxin BuIIIB from Conus bullatus (μ-BuIIIB) was shown to block Na(V)1.3 with sub-micromolar potency (K(d) = 0.2 μM), making it one of the most potent peptidic inhibitors of this subtype described to date. However, oxidative folding of μ-BuIIIB results in numerous folding isoforms, making it difficult to obtain sufficient quantities of the active form of the peptide for detailed structure-activity studies. Here we report the synthesis and characterization of μ-BuIIIB analogs incorporating a disulfide-deficient, diselenide-containing scaffold designed to simplify synthesis and facilitate structure-activity studies directed at identifying amino acid residues involved in Na(V)1.3 blockade. Our results indicate that, like other μ-conotoxins, the C-terminal residues (Trp16, Arg18 and His20) are most crucial for Na(V)1 block. At the N-terminus, replacement of Glu3 by Ala resulted in an analog with increased potency for Na(V)1.3 (K(d) = 0.07 μM), implicating this position as a potential site for modification for increased potency and/or selectivity. Further examination of this position showed that increased negative charge, through γ-carboxyglutamate replacement, decreased potency (K(d) = 0.33 μM), while replacement with positively-charged 2,4-diamonobutyric acid increased potency (K(d) = 0.036 μM). These results provide a foundation for the design and synthesis of μ-BuIIIB-based analogs with increased potency against Na(V)1.3.